Anti‐CD47 monoclonal antibody therapy reduces ischemia‐reperfusion injury of renal allografts in a porcine model of donation after cardiac death. Issue 4 (2nd December 2017) - Xu, Min; Wang, Xuanchuan; Banan, Babak; Chirumbole, Danielle L.; Garcia‐Aroz, Sandra; Balakrishnan, Aparna; Nayak, Deepak K.; Zhang, Zhengyan; Jia, Jianluo; Upadhya, Gundumi A.; Gaut, Joseph P.; Hiebsch, Ronald; et al.
Abstract : We investigated whether blockade of the CD47 signaling pathway could reduce ischemia‐reperfusion injury (IRI) of renal allografts donated after cardiac death (DCD) in a porcine animal model of transplantation. Renal allografts were subjected to 30 minutes of warm ischemia, 3.5 hours of cold ischemia, and then perfused with a humanized anti‐CD47 monoclonal antibody (CD47mAb) in the treatment group or HTK solution in the control group (n = 4/group). The animals were euthanized five days after transplantation. At the time of reperfusion, indocyanine green‐based in vivo imaging showed that CD47mAb‐treated organs had greater and more uniform reperfusion. On post‐transplant days 3‐5, the treatment group had lower values compared to the control for creatinine and blood urea nitrogen. Histological examination of allograft tissues showed a significant decrease of acute tubular injury in the CD47mAb‐treated group compared to control. Compared to the control group, CD47mAb treatment significantly decreased genes expression related to oxidative stress ( sod‐1, gpx‐1, and txn ), the inflammatory response ( il‐2, il‐6, inf‐g, and tgf‐b ), as well as reduced protein levels of BAX, Caspase‐3, MMP2, and MMP9. These data demonstrate that CD47mAb blockade decreases IRI and subsequent tissue injury in DCD renal allografts in a large animal transplant model. Abstract : Antibody‐mediated CD47 blockade in a porcine model of donation after cardiac death improves recipient renal allograft reperfusion, graft function, and histological findings accompanying attenuated oxidative injury, inflammatory cell infiltration, and apoptosis. See the companion article from Wang et al onpage 843 .